Cholesterolosis Bulbi in an Eye with Retinal Capillary Hemangioma: A Rare Association with Chemical Analysis - Aleshawi, Abdelwahab; Al-Dwairi, Rami; Al Qudah, Mohammad; Sharayah, Abdallah; Al Nuaimi, Mahmood; Abu Serhan, Hashem (Case reports in ophthalmology, 2025)
Introduction: Cholesterolosis bulbi is an ocular condition characterized by the accumulation of cholesterol crystals in the vitreous cavity. This case describes the development of anterior chamber cholesterolosis bulbi secondary to retinal capillary hemangioma. Case Presentation: A 26-year-old female, tested negative for von Hippel-Lindau (VHL) syndrome, presented with yellow shinny crystals filling the anterior chamber of the left eye and similar depositions filling the vitreous cavity along with reactivated hemangioma with new feeder vessels. She was diagnosed previously with bilateral capillary retinal hemangiomas. Anterior chamber and vitreous washout and endo-laser photocoagulation for the hemangioma were performed. Analysis of the aqueous sample revealed numerous well-demarcated, rectangular, or polygonal lipid-like crystals on light microscopy. Cholesterolosis bulbi secondary to retinal capillary hemangioma was established. Conclusions: Cholesterolosis bulbi secondary to retinal capillary hemangioma is a rare association and would warrant for extensive tumor or associated complications.